The Effectiveness of Implementing Brain Exercises on Cognitive Function in Elderly with Dementia at Katsuren Hospital Japan - Ningsih, Rizki Yulya; Iqomh, Muhammad Khabib Burhanuddin (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The process of aging and old age is experienced by everyone. Decline in cognitive function in the elderly also often occurs. In the long term, one of the impact of decreased cognitive function is dementia. Dementia is a decline in memory, thinking, behavior and ability to carry out daily activities. The purpose of this case study is to determine the effectiveness of applying brain exercises to elderly people with dementia. This type of research is descriptive using pre-test and post-test methods. The subject in this case study wass an elderly patient with dementia in ward 8 of Katsuren Hospital. The result of the study indicate that the management of nursing care in dementia patients who carried out nursing action of brain exercises therapy for 3 days (10-15 minutes per day), obtained the results of an increase in the ability to remember from Mini Mental State Examination (MMSE) score 21 to 23. From these results it can be concluded that the action of brain exercises therapy is effective in elderly dementia with memory impairment.